AN ANALYSIS OF THE ACTIVITIES IN BAHASA INGGRIS TEXTBOOK FOR GRADE 10th STUDENTS PUBLISHED BY THE INDONESIAN MINISTRY OF EDUCATION AND CULTURE - Intan Permata Sari; An Fauzia Rozani Syafei; Sitti Fatimah (Journal of English Language Teaching, 2018)
This research is an descriptive research that aimed to analyze the quality of the English textbook in term of the activities provided by this book. The object of this research was the Bahasa Inggris textbook for 10th grade students published by the Indonesian Ministry of Education and Culture. This research used an analysis format as the instrument to guide the researcher in analyzing the English textbook. The analysis format contained of six categories which was made based on the principles of good textbook proposed by the experts; the categories are providing the information and opinion gap activities which require the learners to communicate each other, asking the students to make up or write a story, asking the student to make grammatical discoveries from a simple drill, providing readiness activities, providing activities enable the students to recognize language input consciously and subconsciously, and providing activities stimulate the use of both right and left-brain. The result of this research showed that this English textbook can be categorized as good textbook since only one category that was rarely found in this textbook; asking the student to make grammatical discoveries from a simple drill. However, the other criteria had enough number as the activities provided by this book.